2012
DOI: 10.1534/genetics.112.143925
|View full text |Cite
|
Sign up to set email alerts
|

The Am-tra2 Gene Is an Essential Regulator of Female Splice Regulation at Two Levels of the Sex Determination Hierarchy of the Honeybee

Abstract: Heteroallelic and homo- or hemiallelic Complementary sex determiner (Csd) proteins determine sexual fate in the honeybee (Apis mellifera) by controlling the alternative splicing of the downstream gene fem (feminizer). Thus far, we have little understanding of how heteroallelic Csd proteins mediate the splicing of female fem messenger RNAs (mRNAs) or how Fem proteins direct the splicing of honeybee dsx (Am-dsx) pre-mRNAs. Here, we report that Am-tra2, which is an ortholog of Drosophila melanogaster tra2, is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 65 publications
(142 reference statements)
9
90
0
Order By: Relevance
“…In addition to these domains and in contrast to fem, csd is characterized by the hypervariable region (HVR), forming repeated structures of species-specific amino acid motifs that are highly variable in length (Hasselmann et al, 2008b). Heterozygous csd is required to induce the female pathway by interacting with transformer 2 (Nissen et al, 2012), leading to a female-spliced fem transcript; this decision is maintained throughout the development by a positive feedback loop. Homozygous or hemizygous csd induces the male pathway, mediated by a truncated Fem protein, which results from an early stop codon in the male fem mRNA (Beye et al, 2003;Gempe et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these domains and in contrast to fem, csd is characterized by the hypervariable region (HVR), forming repeated structures of species-specific amino acid motifs that are highly variable in length (Hasselmann et al, 2008b). Heterozygous csd is required to induce the female pathway by interacting with transformer 2 (Nissen et al, 2012), leading to a female-spliced fem transcript; this decision is maintained throughout the development by a positive feedback loop. Homozygous or hemizygous csd induces the male pathway, mediated by a truncated Fem protein, which results from an early stop codon in the male fem mRNA (Beye et al, 2003;Gempe et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, csd and fem are paralogs specific to the honeybee lineage (Hasselmann et al 2008) that have evolved and acquired distinct roles in the sex determination pathway. To alleviate confusion when discussing orthologs from different species, genes from the honeybee will be designated with an "Am-" prefix (for A. mellifera, as in Nissen et al 2012). Gene names are written in lowercase italics (e.g., Am-dsx) and protein names in non-italics with the first letter of the protein capitalized (e.g., Am-Dsx).…”
Section: The Buzz On Important Gene Terminologymentioning
confidence: 99%
“…A sequence homology search of the honeybee genome (Dearden et al 2006) previously identified a tra-2 ortholog; however, whether this gene is expressed or produces functional transcripts has not been demonstrated. Therefore, since tra-2 and Am-tra-2 are orthologs, the objective addressed by Nissen et al (2012) was to determine whether Tra-2 and Am-Tra2 share the same function (i.e., regulating sex-specific splicing of dsx) in the fruit fly and in the honeybee.…”
Section: The Objective Of the Studymentioning
confidence: 99%
See 2 more Smart Citations